WORLD PUBLIC OPINION AS THE NEWEST FACTOR OF THE SYSTEM OF INTERNATIONAL RELATIONS - Vadim Gadzhievich Seyidov (Современная наука и инновации)
The article analyzes the problem of public opinion as an important factor of international relations. A thorough theoretical and methodological overview of the study of the phenomenon of public opinion. Critically examine the various definitions, analyzes the features and functions of public opinion, it is theoretically proved that public opinion is an integral element of world politics. The estimation ofthe activities of the various international centres dedicated to the study of public opinion. Outlines the General theoretical conclusions on the research question.